2017
DOI: 10.34058/njmr.v19i1.167
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Physiotherapists in Primary Health Care in Nigeria

Abstract: Summary: This paper examines the concept, strength and weakness of Primary health care system (PHC) program in Nigeria, the opportunity and potential roles for physiotherapists in PHC delivery system as well as the perceived benefits of integrating physiotherapy profession into PHC delivery system in Nigeria.Currently, physiotherapy services are available at the big cities in the urban areas of the country, thus denying the myriads of people that might need the service that could not get to the big cities eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…For instance, the patient/clinician ratio for physiotherapy in Nigeria is 0.047 per 1000 of the population ( 40 ). Currently, physiotherapy services have not been incorporated into primary health-care services; therefore, every patient who requires physiotherapy is referred to either the secondary or the tertiary care centers except for a few who can afford the private facilities ( 41 ). As a result of this over dependence on the physiotherapy service at the secondary and tertiary level, the patient caseload as well as the wait time is likely to continue across various clinics in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the patient/clinician ratio for physiotherapy in Nigeria is 0.047 per 1000 of the population ( 40 ). Currently, physiotherapy services have not been incorporated into primary health-care services; therefore, every patient who requires physiotherapy is referred to either the secondary or the tertiary care centers except for a few who can afford the private facilities ( 41 ). As a result of this over dependence on the physiotherapy service at the secondary and tertiary level, the patient caseload as well as the wait time is likely to continue across various clinics in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, rehabilitation services by the therapists are often accessed only in secondary and tertiary facilities in the urban centers, with little or no community rehabilitation services [7]. Recently, it has been suggested that, there are opportunities for rehabilitation therapists to play important roles at the primary healthcare level in the country [8]. However, even this may not be able to adequately cater for the rehabilitation needs of children with CP since they may require care 24/7.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, rehabilitation services by the therapists are often accessed only in secondary and tertiary facilities in the urban centers, with no or little community rehabilitation services (7). Recently, it has been suggested that, there are opportunities for rehabilitation therapists to play important roles at the primary healthcare level (8).…”
Section: Introductionmentioning
confidence: 99%